KINETICS OF CALCITE GROWTH: SURFACE PROCESSES AND RELATIONSHIPS TO MACROSCOPIC RATE LAWS - Teng H.H.; Dove P.M.; De Yoreo J.J. (My University, 2000)
This study links classical crystal growth theory with observations of microscopic surface processes to quantify the dependence of calcite growth on supersaturation, σ, and show relationships to the same dependencies often approximated by affinity based expressions. In situ Atomic Force Microscopy was used to quantify calcite growth rates and observe transitions in growth processes on {10 4} faces in characterized solutions with variable σ. When σ < 0.8, growth occurs by step flow at surface defects, including screw dislocations. As σ exceeds 0.8, two-dimensional surface nucleation becomes increasingly important. The single sourced, single spirals that are produced at lower σ were examined to measure rates of step flow and the slopes of growth hillocks. These data were used to obtain the surface-normal growth rate, Rm, by the pure spiral mechanism.